1993
DOI: 10.1152/ajpgi.1993.265.4.g752
|View full text |Cite
|
Sign up to set email alerts
|

Role of histamine2 receptor in increased expression of rat gastric H(+)-K(+)-ATPase alpha-subunit induced by omeprazole

Abstract: Omeprazole is a specific inhibitor in vivo of the functioning gastric acid pump, the H(+)-K(+)-adenosinetriphosphatase (ATPase), in the secretory canaliculus of the parietal cell. It has been shown previously that omeprazole in rats led to an increase in the mRNA for the alpha-subunit of the H(+)-K(+)-ATPase. Omeprazole causes a marked increase in circulating gastrin in this species, which in turn stimulates release of histamine from the enterochromaffin-like cell. The possible role of this pathway was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…There is also some experimental evidence that potent acid suppression may upregulate the H + , K + -ATPase. 37 However, this effect seems to be mediated via the histamine H 2 -receptor, 37 supporting the hypothesis outlined above. Moreover, other studies indicate that H + , K + -ATPase mRNA does not change during dosing with proton pump inhibitors for longer periods of time.…”
Section: Tolerance To Acid-inhibitory Drugsmentioning
confidence: 67%
See 1 more Smart Citation
“…There is also some experimental evidence that potent acid suppression may upregulate the H + , K + -ATPase. 37 However, this effect seems to be mediated via the histamine H 2 -receptor, 37 supporting the hypothesis outlined above. Moreover, other studies indicate that H + , K + -ATPase mRNA does not change during dosing with proton pump inhibitors for longer periods of time.…”
Section: Tolerance To Acid-inhibitory Drugsmentioning
confidence: 67%
“…If acid suppressive treatment has been given for a long period of time, it is possible that an increased parietal cell mass 34,35 or an upregulated H + , K + -ATPase activity 37 could partially explain post-treatment rebound acid hypersecretion. The animal studies described above indicate that this is not the case, 37, 38 although we presently lack experimental studies in humans addressing this question.…”
Section: Rebound Acid Hypersecretionmentioning
confidence: 99%
“…[30][31][32] Based on earlier reports, one of the pathways that stimulates ATPase gene expression is as follows: gastrinAEgastrin/CCK-B receptor of ECL cellsAE histidine decarboxylase gene activationAEhistamineAE H 2 receptor of parietal cellsAEcAMP/intracellular calcium concentration ([Ca 2Ļ© ]i) AEH Ļ© , K Ļ© -ATPase gene activation, and morphological activation (stimulation). [27][28][29] The present study demonstrated that the histamine content of the fundic mucosa was higher with omeprazole treatment than with rabeprazole treatment. In addition, the increase in H Ļ© , K Ļ© -ATPase mRNA was markedly greater with omeprazole treatment than with rabeprazole treatment, and the difference was significant at a dose of 100mg/kg.…”
Section: Discussionmentioning
confidence: 79%
“…27 Thus, the elevation of histamine, not gastrin, is the most significant factor promoting an increase in ATPase gene expression and the transformation of parietal cells to a more stimulated state. 27,28 Our previous experiments have also demonstrated that the morphological activation of parietal cells induced by hypergastrinemia, and the subsequent increase of H Ļ© , K Ļ© -ATPase synthesis by these cells, are mediated by an increase in histidine decarboxylase gene expression in ECL cells that is stimulated through the gastrin/cholecystokinin (CCK)-B receptor. 29 Miyazaki et al 30 have suggested that the massive urinary excretion of histamine caused by treatment with rabeprazole reflects the gastrin-induced mobilization of gastric histamine, and that neither rabeprazole itself nor rabeprazole-induced luminal pH elevation directly promotes the mobilization of oxyntic mucosal histamine.…”
Section: Discussionmentioning
confidence: 99%
“…In rat parietal cells, the hypergastrinemia induced by multiple doses of omeprazole causes a significant increase in H Ļ© -K Ļ© -adenosine triphosphatase (ATPase) gene expression 9 and in the number of morphologically fully stimulated parietal cells, in which the proton pump protein has moved into the apical membrane. 10 In the rabbit, blocking H Ļ© -K Ļ© -ATPase by omeprazole enhances the degradation and macrophage-mediated elimination of parietal cells, and also causes an increase in parietal cell production.…”
Section: Introductionmentioning
confidence: 99%